Identification of Students' Misconceptions on Acid-Base using Four Tier Diagnostic Tests - Fahmiya Aini; Ifah Silfianah (Universitas Negeri Malang, 2022)
Students often have difficulty understanding acid-base material, so it has the potential to cause misconceptions. If the students' misconceptions are left unattended and not immediately identified, there will be ongoing misconceptions. This study aimed to describe the misconceptions that occur in acid-base material and determine the large percentage of students who experience misconceptions. The method used in this research is descriptive quantitative. The subjects of this study consisted of 108 students of class XII MA Matholi'ul Anwar. The identification of misconceptions used a four-tier diagnostic test instrument with 20 items. The students' answers from the test were then analyzed and categorized into understanding concepts, not understanding concepts, and misconceptions. This study found that 50% of students hold misconceptions about acid-base theories, 59% in acid-base indicators, 55% in acid-base ionization constant, 58% in pH, 55% in the calculation of pH and 51.9% in pH concepts in the environment.